How parents describe picky eating and its impact on family meals: A qualitative analysis. (1st March 2017) - Trofholz, Amanda C.; Schulte, Anna K.; Berge, Jerica M.
Abstract: Children are frequently described as being picky eaters. However, this term has been inconsistently defined in prior research. There is limited qualitative research investigating how parent's define picky eating, how they respond to it, or how they see picky eating impacting their child's dietary intake or the family meal. For this study, parents (n = 88) of siblings (ages 2–18 years old) were interviewed in their homes. The semi-structured interviews focused on parent feeding practices and child eating behaviors. A qualitative content analysis approach was used to analyze the data; themes regarding picky eating emerged. Results of this study show that the majority of parents (94% female; mean age 35 years) were from minority and low income homes. The following themes regarding picky eating were identified: 1) children were frequently described as being picky eaters; 2) parents defined picky eating in a variety of ways (i.e., not liking a few foods; limited intake; resisting texture or appearance of foods; resistance to new foods); 3) picky eating impacted the family meal (i.e., promotes meal-related parent stress; impacts meal preparation); and 4) parents responded to picky eating in a variety of ways (i.e., require child tries food; allow child to make separate meal; allow child not to eat; parent makes a separate meal; allows child to choose only food he/she likes; requires child to eat anyway). This study demonstrates that many parents experience child picky eating and report that it impacts family meals. Additionally, study results provide information on the specific ways pickiness impacts the family meal and how parents respond to pickiness. This study also provides guidance for future studies wishing to define picky eating or evaluate the prevalence of child pickiness.